The Relationship between Self-Efficacy, Kinesiophobia, and Physical Activity in People with Heart Failure: A Systematic Review and Meta-Analysis - Hoang, Thi Ngoc Anh; Sasat, Siriphan (National Journal of Community Medicine, 2026)
Background: In heart failure (HF), self-efficacy facilitates physical activity (PA), whereas kinesiophobia is known as a barrier to PA. Understanding their relationship with PA may support the effectiveness of interventions to enhance PA performance in HF patients. The objective was to investigate the strength of the relationship between self-efficacy, kinesiophobia, and PA in HF patients. Method: Five databases were used to search for eligible articles, including PubMed, Scopus, ScienceDirect, ProQuest and CINAHL from 2015 to 2025. Six correlations were included in the meta-analysis between self-efficacy and PA, and the other five articles were analyzed in the kinesiophobia and PA meta-analysis. Results: Self-efficacy was associated positively with PA (pooled r = 0.29, 95%CI: 0.22 to 0.36), while kinesiophobia was associated negatively with PA (pooled r = -0.33, 95%CI: -0.45 to -0.21). Exercise-task self-efficacy had a higher relationship to PA (pooled r = 0.31, 95%CI: 0.23 to 0.39). Kinesiophobia measured by FActS-HF had a higher relationship to PA compared to the other. pooled r = - 0.37 (95%CI: -0.59 to -0.15). Conclusion: Both kinesiophobia and self-efficacy have a moderate relationship with PA in HF. These results highlight the significance of psychological factors, including self-efficacy and kinesiophobia in the PA of individuals with HF.